EXTRACORPORAL CARDIOPULMONARY RESUSCITATION (ECPR) FOLLOWING PULMONARY ARTERY RUPTURE IN AN INFANT - I. A. Kornilov; I. A. Soynov; A. V. Zubritsky; Yu. Yu. Kulyabin; S. M. Ivantsov; A. V. Gorbatykh; N. R. Nichay; A. Yu. Omelchenko (Инновационная медицина Кубани)
The rupture of the pulmonary artery during balloon valvular dilatation is rare and the severest complication. In this clinical case we described the rupture of the pulmonary artery in a 10-month-old baby with cardiac tamponada and an extreme hemodilution due to blood loss. CPR has been using for 40 minutes but being ineffective. For 3 days we have been applying ECMO. This patient was discharged without any neurological disorders.